Approximating fixed points of nonexpansive type mappings - Hemant K. Pathak; Mohammad S. Khan (International Journal of Mathematics and Mathematical Sciences)
In a uniformly convex Banach space, the convergence of Ishikawa iterates to a unique fixed point is proved for nonexpansive type mappings under certain conditions.